New species of Pseudophyllinae specially from Brazil (Orthoptera, Tettigoniidae) - Piza Jr., S. de Toledo (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1980)
In this paper, the following new species of Pseudo-phyllinae (Orthoptera-Tettigoniidae) are drescribed, to one of which a new genus was erected: Brachyauchenus varicosus, Entaoanthodes tesselatus, Eumecoptevus vetus, Glaphyraspis beieri; Gongroonemis belemita, Gongroonemis montana, Gogrocnemis suvinomaò Gimenesia inoognita, Pavaemesia pavaibana(n. g.), and Scopiorinus turrialbae.